Congenital malaria presenting as late-onset sepsis in infant with mother treated with antimalarial therapy: A case report - Bhageria, Prachi; Dhyani, Anuj; Gupta, Vipul; Gupta, Arvind; Sharma, Seshendra (Indian Journal of Child Health, 2019)
Incidence of congenital malaria has been reported to be in the range between 0.3% and 30% in both the endemic and non-endemic areas. Malaria in pregnancy and congenital malaria are epidemiologically less investigated in India. Timely intervention and awareness are necessary for desirable outcome and prevention of the condition and to prevent perinatal and maternal morbidity and mortality. Herein, we report a case of a 1-month-old male baby, presenting with high-grade fever, feeding difficulty, and hepatosplenomegaly on examination. Mother had a history of chills and rigors in her first trimester and was found to be smear positive for Plasmodium vivax. Investigations of the child revealed thrombocytopenia, raised C-reactive protein and positive peripheral smear for P. vivax. She was treated with Inj. artesunate and cured. Thus, congenital malaria should be considered as a differential diagnosis in newborn presenting with clinical features of sepsis even when mother has been adequately treated.